Transportation applications for developing tourist enclaves: Lessons from Koh Lanta, Thailand - Brittany Nikole Montgomery (University of California, Institute of Urban and Regional Development (IURD), 2008)
The successful development of island-based tourism is largely dependent on the type of transportation access available to carry people and goods to the island. If transportation access is not planned and managed carefully, it can contribute to the destruction of both the environment and communities that first attracted tourists. Koh Lanta Yai in Krabi Province, Thailand presents a prime example of the transportation pressures caused by rapid tourism growth. The economic, environmental, and social outcomes of these choices will help determine the type of tourism that Lanta supports. This paper outlines two transportation alternatives, the choice of which will determine the shape and rate of development on Lanta Yai. Key transportation planning lessons can be drawn from the Lanta case, which are applicable not only to tourist islands, but to any growing tourist destination. These include aspects of community need, financial support for alternatives, limited car use, and hotel owner collaboration for transportation initiatives.
Keywords: 330